2005
DOI: 10.1159/000084270
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in vitro Susceptibilities of Ocular Bacterial Isolates to Gatifloxacin and Other Topical Antibiotics

Abstract: Purpose: To compare the in vitro activity of gatifloxacin with that of other topical antibiotics against fresh bacterial isolates from various types of human ocular infections. Methods: A total of 498 strains of ocular bacterial isolates were tested for their susceptibility to gatifloxacin, ofloxacin, ciprofloxacin, norfloxacin, gentamicin, tobramycin, neomycin, chloramphenicol, erythromycin, tetracycline and amikacin. Results: Ninety-nine percent of gram-positive and 92% of gram-negative bacterial strains wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 42 publications
4
19
0
Order By: Relevance
“…13,14 Studies have shown that topical gatifloxacin solution may be effective in prevention of infectious conditions such as conjunctivitis, keratitis, and postcataract endophthalmitis. 15,16 Owing to the benefits offered by gatifloxacin, various manufacturers have introduced gatifloxacin eyedrops (0.3% wt/vol). Fluoroquinolones have pHdependent solubility.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Studies have shown that topical gatifloxacin solution may be effective in prevention of infectious conditions such as conjunctivitis, keratitis, and postcataract endophthalmitis. 15,16 Owing to the benefits offered by gatifloxacin, various manufacturers have introduced gatifloxacin eyedrops (0.3% wt/vol). Fluoroquinolones have pHdependent solubility.…”
Section: Introductionmentioning
confidence: 99%
“…It has superior efficacy. Studies have shown that a topical gatifloxacin solution may be effective in prevention of infectious conditions such as conjunctivitis, keratitis, and post-cataract endophthalmitis [12]. Fluconazole (2-(2,4-diflurophenyl)-1,3-bis(1H-1,2,4-triazol-1-yl)propan-2-ol) is a popular antifungal drug belonging to the third generation of azole derivatives.…”
mentioning
confidence: 99%
“…42,43 The percentage of P aeruginosa isolates showing resistance to ciprofloxacin increased from less than 1.0% of isolates obtained from 1991 to 1994 to 4.4% of those obtained from 1995 to 1998 44,45 and to 29% of those obtained from 2002 to 2003. 31 In the same time periods, the rates of resistance to gentamicin increased from less than 1% to 18%. 31,45 31,42 However, coagulase-negative staphylococci isolates from separate studies ending in 2006 identified rates of resistance to gatifloxacin of 11.6% in normal ocular bacterial flora 47 and of 53% in coagulase-negative staphylococci endophthalmitis isolates.…”
Section: Fluoroquinolone Resistance Mechanismsmentioning
confidence: 95%
“…31 In the same time periods, the rates of resistance to gentamicin increased from less than 1% to 18%. 31,45 31,42 However, coagulase-negative staphylococci isolates from separate studies ending in 2006 identified rates of resistance to gatifloxacin of 11.6% in normal ocular bacterial flora 47 and of 53% in coagulase-negative staphylococci endophthalmitis isolates. 48 A study of resistance patterns to ocular coagulase-negative staphylococci isolates in Brazil over a 15-year period found that resistance to gentamicin and tobramycin increased from nothing in conjunctival isolates obtained from 1985 to 1988 to 13% and 11%, respectively, in isolates obtained in 1997 and 2000.…”
Section: Fluoroquinolone Resistance Mechanismsmentioning
confidence: 95%
See 1 more Smart Citation